Implementasi Program Holistik Integratif Untuk Peningkatan Kualitas Paud Di Kabupaten Wajo - Rifanti, Andi Irna; Tolla, Ismail; Ardiansyah, Muh (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study aims to examine the implementation of the Holistic Integrative Program to improve the quality of early childhood education (PAUD) management at KB Tunas Harapan, located in Lampulung Village, Pammana District, Wajo Regency. The research describes how the Holistic Integrative Early Childhood Education (PAUD HI) Program is implemented to enhance PAUD management quality and identifies the supporting and inhibiting factors. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results show that KB Tunas Harapan has successfully implemented PAUD HI across five service dimensions: health and nutrition, education, parenting, protection, and welfare. Supporting factors include the commitment of school leaders and teachers, collaboration with parents and the community, and the availability of infrastructure. Inhibiting factors include limited human resources, low parental understanding, and budget constraints. This study recommends improving the quality and quantity of human resources, enhancing parental understanding, optimizing budget management, strengthening government policy support, and increasing community education regarding the importance of PAUD HI.